2020
DOI: 10.1186/s12879-020-05589-0
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of HIV self-testing is low among men who have sex with men who have not tested for HIV: a study with respondent-driven sampling in Brazil

Abstract: Background Brazil has many people living with HIV (PLWH) who are unaware of their serostatus. The public health system has recently added HIV self-testing (HIVST) for key populations such as men who have sex with men (MSM). This study estimates HIVST acceptability among Brazilian MSM and explores factors associated with acceptability among MSM who have never tested for HIV or who had a previous negative result. Methods Respondent-driven sampling (R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
3
7
1
1
Order By: Relevance
“…According to our findings, only 65.9% of MSM in our study had ever self-tested for HIV. Our observed rate is higher than the rates found in a study conducted in the province in 2014 (26.2%) ( 24 ), and in recent studies conducted in Brazil (49.1%) ( 13 ) and China ( 25 ). Considering the limitations of facility-based testing and the impact of COVID-19, upscaling HIVST uptake among Chinese MSM will require more efforts.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…According to our findings, only 65.9% of MSM in our study had ever self-tested for HIV. Our observed rate is higher than the rates found in a study conducted in the province in 2014 (26.2%) ( 24 ), and in recent studies conducted in Brazil (49.1%) ( 13 ) and China ( 25 ). Considering the limitations of facility-based testing and the impact of COVID-19, upscaling HIVST uptake among Chinese MSM will require more efforts.…”
Section: Discussioncontrasting
confidence: 85%
“…In addition, many studies have found HIVST acceptable to various marginalized populations (including MSM) and feasible in multiple settings (11)(12)(13)(14). For MSM who have never tested for HIV, HIVST may represent a suitable option as it offers privacy, confidentiality, and is easy to use (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing recognition that knowledge about HIV prevention modalities facilitates their uptake. 14 Research has shown that those with greater HIV knowledge are more likely to engage with prevention services, 15 and lack of understanding about the efficacy and/or side effects of PrEP may lead to decreased willingness to use it. 16 Another factor known to impact engagement with HIV prevention is internalized homonegativity, which refers to gay or homosexual MSM directing societal stigma, discrimination, or negative perceptions about homosexuality toward themselves.…”
Section: Introductionmentioning
confidence: 99%
“…This lower HIV knowledge may be a contributing factor to higher vulnerability to HIV infection. Indeed, multiple studies using different measures of HIV-related knowledge have shown a link between testing and knowledge with a gradient of increased knowledge as you move from the categories of never tested to HIV-negative and HIV-positive [ 28 , 29 , 56 ]. One hypothesis for this finding is that exposure to the health care setting and counseling during testing may increase HIV-specific knowledge.…”
Section: Discussionmentioning
confidence: 99%